The relationship between the occurrence of psoriasis and depression - Karolina Obuchowska; Aleksandra Obuchowska; Arkadiusz Standyło; Justyna Wójcik; Alicja Ozga (Kazimierz Wielki University, 2020)
Psoriasis (skin psoriasis, PsO) is a chronic auto‐immune skin inflammatory condition. In about one-third of cases, the joints are affected (psoriatic arthritis, PsA). Both conditions, especially PsA, profoundly impact patients' health-related quality of life.  This disease affects between 2% and 3% of the population. The onset occurs before the age of 40 as a sharply demarcated scaly, red skin lesions, most often on the elbows, knees, scalp, hands, feet and joints considering osteoarticular involvement. Patients are suffering from itching, irritations, stinging and pain. Etiology of this disease is multifactorial, with genetic and environmental involvement, psychological stress and depression being the key factors considering the onset, flare or therapeutic resistance of psoriatic disease. The purpose of this article is to review and analyze how depression and stress affect the life of patients with psoriasis and in which way prevention could play a role regarding the evolution of this disease. Proinflammatory cytokines such as interleukin (IL)‐1 and IL‐6 are elevated in both psoriasis and depression, indicating that the inflammatory process may be involved in the progression of both diseases. Psoriasis has long been recognized to be associated with potentially adverse effects on mental health. However, there have been relatively few studies evaluating psychological outcomes in patients with psoriasis. Depression and stress decrease the quality of life, psoriasis being the last drop in the glass, with bimodal intensification of these pathologies. Quality of life in patients with psoriasis is directly associated with the severity of the disease, family status, work status and stigmatization.